Effect of Elevated Reperfusion Pressure on "No Reflow" Area and Infarct Size in a Porcine Model of Ischemia–Reperfusion. (July 2016) - Pantsios, Chris; Kapelios, Chris; Vakrou, Styliani; Diakos, Nikolaos; Pozios, Iraklis; Kontogiannis, Chris; Nanas, John; Malliaras, Konstantinos
Background: The "no reflow" phenomenon (microvascular obstruction despite restoration of epicardial blood flow) develops postreperfusion in acute myocardial infarction and is associated with poor prognosis. We hypothesized that increased reperfusion pressure may attenuate the no reflow phenomenon, as it could provide adequate flow to overcome the high resistance of the microvasculature within the no reflow zone. Thus, we investigated the effect of modestly elevated blood pressure during reperfusion on the extent of no reflow area and infarct size in a porcine model of ischemia–reperfusion. Methods: Eighteen farm pigs underwent acute myocardial infarction by occlusion of the anterior descending coronary artery for 1 hour, followed by 2 hours of reperfusion. Just prior to reperfusion, animals were randomized into 2 groups: in group 1 (control group, n = 9), no intervention was performed. In group 2 (n = 9), aortic pressure was increased by ∼20% (compared to ischemia) by partial clamping of the ascending aorta during reperfusion. Following 2 hours of reperfusion, animals were euthanized to measure area at risk, infarct size, and area of no reflow. Results: Partial clamping of the ascending aorta resulted in modest elevation of blood pressure during reperfusion. The area at risk did not differ between the 2 groups. The no reflow area was significantly increased in group 2 compared to control animals (50% ± 13% vs 37% ± 9% of the area at risk; P = .04). The infarcted area was significantly increased in group 2 compared to control animals (75% ± 17% vs 52% ± 23% of the area at risk; P = .03). Significant positive correlations were observed between systolic aortic pressure and no reflow area, between systolic aortic pressure and infarcted area and between infarcted area and no reflow area during reperfusion. Conclusions: Modestly elevated blood pressure during reperfusion is associated with an increase in no reflow area and in infarct size in a clinically relevant porcine model of ischemia–reperfusion.